50‐4: A Novel Evaluation Method for Short‐Residual Image of AMOLED Display. Issue 1 (29th May 2019) - Peng, Jintao; Peng, Kuanjun; Zhang, Fangzhen; Sun, Shuang; Niu, Jing; Zhou, Tingting; Niu, Yanan; Shi, Lubin; Ren, Jinyu
Abstract : The hysteresis behavior in TFTs caused short‐residual image of AMOLED Display. Hysteresis and optical method are two kinds of traditional evaluation methods. In the practical operation, hysteresis method is not sufficient, and optical method need a product after module process, which has some limitations, such as high production costs, long cycle. In this paper, we provide a novel evaluation method, which can match well with the results of hysteresis and optical method. The novel evaluation has an advantage in accuracy, production costs and cycle, compared with traditional method.